Children’s semiotic and multimodal meaning-making in numerical story problems - Sukmawati Firdaus Sagran; Sukmiyati Firdaus Sagran; Lisa Gildner (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Islam Malang, 2026)
This study addresses a gap in early childhood mathematics research: while previous studies have largely emphasized number-symbol representation and correct answers, limited attention has been paid to children’s semiotic, multimodal, and meaning-making processes when solving numerical story problems. This study employs a descriptive qualitative approach. Data were collected through observation of children while working on numerical story problems, interviews with teachers regarding how children learn, and documentation of scribbles, drawings, and mathematical symbols produced by children. This study was conducted with 25 kindergarten children aged 5–6 years (Group B) at RA Anggrek. Data were collected through classroom observations, contextual interviews with children and teachers, and documentation of children’s drawings, scribbles, gestures, verbal counting, and mathematical symbols. The findings show that children predominantly used drawings as primary semiotic representations, accompanied by gestures, verbal counting, scribbles, and emerging use of number symbols. These modes did not appear separately; rather, they interacted dynamically as thinking tools in the children’s meaning-making process. The child's meaning-making process toward the signs they created shows that these representations function as thinking tools. From Vygotsky's perspective, the Zone of Proximal Development (ZPD) emerges when children transition from concrete to abstract thinking, whereas according to Piaget, children are in the preoperational stage, which still relies on concrete objects. This study highlights that children’s mathematical understanding develops through multimodal semiotic activity, not merely through formal symbols or final answers. Pedagogically, the findings suggest that early childhood numeracy instruction should provide space for drawing, moving, marking, and talking as legitimate parts of mathematical thinking.